Pengaruh Motivasi Kerja, Kepuasan Kerja Dan Lingkungan Kerja Terhadap Produktivitas Karyawan PT. Literindo Berkah Karya - Mobaraq, Moh. Rizki Fajar; Sunaryo, Hadi; Mustapita, Arini Fitria (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to determine and analyze the influence of work motivation, job satisfaction and work environment on employee productivity at PT. Literindo Berkah Karya. Employee productivity. Employee productivity can be interpreted as a tool for assessing the comparison between the quality and quantity of an employee's work or work that has been completed. This research is explanatory research with a quantitative approach. This research collected data from 30 respondents who were employees of PT. Literindo Berkah Karya. The variables studied include work motivation, job satisfaction, and work environment.The research results show that work motivation, job satisfaction, and work environment have a significant effect on employee productivity, work motivation has a significant effect on employee productivity, job satisfaction has no effect on employee productivity, work environment has no effect on employee productivity. This research suggests that companies provide job promotions, give appreciation to employees, and improve work facilities to increase employee productivity at work. Keywords: Work Motivation, Job Satisfaction, Work Environment, Employee Productivity